PENGARUH MENGIKUTI UNIT BISNIS TERHADAP PENINGKATAN KETERAMPILAN DAN MOTIVASI BERWIRAUSAHA PADA SANTRI - Deni Anggrayani; Ari Susanto; Safiruddin Al Baqi (MA'ALIM: Jurnal Pendidikan Islam, 2020)
As education systems, Islamic boarding school has several advantages such as teaching religious knowledge, science and various extracurricular activities. Modern Islamic Boarding School of Darussalam GontorInodonesia is a boarding school that has a holistic education system, which is not only educate the academic skill but also educate students in developing entrepreneurship skills. This study aims to determine the effect of joining the business unit to the motivation and ability of entrepreneurship among students. This research used ethnography method with interviews and observations in business units in Darussalam Gontor. The results of this study indicate that Darussalam Gontoris a boarding school which implements 24-hour education system with various activities, such as praying togather, muajjah, learning in class, sports, mahkamatullughohand others. Differences of Darussalam Gontor with other boarding school is because Darussalam Gontor requires senior student to be responsible for business unit, such as Darussalam Press, Wisma Darussalam, La Tansa bookstore and other units. Result of this study shows that after joining the business unit, students become more motivated to develop their own business. Students also get enough knowledge to start a business or become an entrepreneur. The data showed that many alumni who have success become entrepreneurs. The entrepreneur character is heavily influenced by the role of alumni as a student of Darussalam Gontor. The alumni's businesses include production of songkok, ice cream, bookstore, travel agent, garment businessman and others. Keywords: Business unit, education system, entrepreneurship, Islamic boarding school, Islamic education